Cervico-Vaginal Smear Abnormalities in a Patient with Pemphigus Vulgaris - Zheng Yuan; Ng Yen Ching Yeo; Ieera Madan Aggarwal (Journal of Cervical Cancer, 2024)
Pemphigus vulgaris is an autoimmune-mediated blistering disease. Cervical involvement is rare. A 38 year old nulliparous woman with PV on oral prednisolone and azathioprine was referred to the Gynaecology service for an abnormal cervical cytological smear showing low-grade squamous intraepithelial lesion. She was asymptomatic, 10 pack-year smoker, and reported no abnormal vaginal bleeding. Colposcopy was unsatisfactory with inadequate visualisation of the transformation zone due to severe cervico-vaginitis. A small focus of aceto-white epithelium was seen, surrounded by peeling, friable epithelium. HPV DNA test was negative. Punch biopsy demonstrated metaplastic squamous epithelium with intraepidermal suprabasal blister formation with acantholysis. Well-vascularised dermal papillae lined residual basal cells, giving rise to a tombstone appearance. There was no evidence of CIN/CGIN or invasive malignancy. An ulcer was also seen in the left buccal region. Repeat colposcopy after 6 weeks showed a small ulcerated area at the biopsy site with rolled healing edges, and a separate small ulcer. Cervical smear and colposcopy 6 months later were unremarkable. The incidence of cervical pemphigus vulgaris may be underestimated because women with pemphigus are often managed by Dermatologists without gynaecological input. In many published cases, cervical involvement was only detected after gynaecological examination due to symptoms such as dyspareunia, post-coital bleeding or vaginal discharge. Cervical smears of patients with pemphigus vulgaris typically display acantholysis, which may be misinterpreted as reparative, inflammatory, or neoplastic change. There have been reports of unnecessary hysterectomy due to such misdiagnoses. Review by an experienced cyto-pathologist is required in the event of diagnostic uncertainty.
Keywords: Pemphigus vulgaris